STRUKTUR SURAT AL-HIJR PERSPEKTIF SEMITIC RHETORICAL ANALYSIS (SRA - Abdullah Muhammady,; Abu Bakar; Suqiyah Musafa’ah; Aqdi Rofiq Asnawi (Institut Dirosat Islamiyah Al-Amien Prenduan, 2022)
The Quran contains verses and letters that are systematically and coherently structured, as supported by al-Zarkashi and al-Suyuti. But Richard Bell took a different view. For example, according to him, the letter Al-Hijr needed to be more systematic, and there were some errors in laying verses. Meanwhile, Michel Cuypers is serious about the Semitic Rhetorical Analysis (SRA) approach in analyzing the structure of the Qur'anic text to find a concentric, mirror, and parallel symmetrical patterns in the form of the Qur'anic text. Even this approach is Considered a modern methodology with a new type of dialogue. It is interesting to look for bright spots in the structure of surat al-Hijr from the perspective of SRA. So that raises the question of what is the form of the text of surat al-Hijr from the standpoint of SRA. A Semitic Rhetorical Analysis (SRA) approach is used to answer this question. That is by analyzing the pairing pattern of the text of surat al-Hijr so that it forms groups of text at the bottom level. The bottom level has reanalyzed the design to get groups of text at the level above it, and so on, until the top level is obtained, namely surat al-Hijr. This article concludes that SRA, according to surat al-Hijr, is a Book consisting of 13 Sections arranged in a concentric symmetrical pattern (A-B-C-B*-A*). Richard Bell's opinion is refuted because each verse in surah al-Hijr is capable of symmetry with other poems from the lowest level of the text to the top level, so this conclusion indicates that surat al-Hijr is systematically and Coherently arranged.